PANoptosis: A New Insight Into Oral Infectious Diseases - Jiang, Weiyi; Deng, Zilong; Dai, Xingzhu; Zhao, Wanghong (Frontiers in Immunology, 2021)
The oral microbiome, one of the most complex and intensive microbial ecosystems in the human body, comprises bacteria, archaea, fungi, protozoa, and viruses. Dysbiosis of the oral microbiome is the initiating factor that leads to oral infectious diseases. Infection is a sophisticated biological process involving interplay between the pathogen and the host, which often leads to activation of programmed cell death. Studies suggest that pyroptosis, apoptosis, and necroptosis are involved in multiple oral infectious diseases. Further understanding of crosstalk between cell death pathways has led to pyroptosis, apoptosis, and necroptosis being integrated into a single term: PANoptosis. PANoptosis is a multifaceted agent of the immune response that has important pathophysiological relevance to infectious diseases, autoimmunity, and cancer. As such, it plays an important role in innate immune cells that detect and eliminate intracellular pathogens. In addition to the classical model of influenza virus-infected and Yersinia-infected macrophages, other studies have expanded the scope of PANoptosis to include other microorganisms, as well as potential roles in cell types other than macrophages. In this review, we will summarize the pathophysiological mechanisms underlying inflammation and tissue destruction caused by oral pathogens. We present an overview of different pathogens that may induce activation of PANoptosis, along with the functional consequences of PANoptosis in the context of oral infectious diseases. To advance our understanding of immunology, we also explore the strategies used by microbes that enable immune evasion and replication within host cells. Improved understanding of the interplay between the host and pathogen through PANoptosis will direct development of therapeutic strategies that target oral infectious diseases.